A proposed beach resort and recreational complex - Camposano, Deo G. (Manila : National University, 2001)
This natural attraction will be one of the tourist attraction in our country. To further develop and improve this idealic view, a proposed project will surface and this will be the "Cabugao Beach Resort and Recreational Complex".